Incidence and clinical variables associated with streptococcal throat infections: a prospective diagnostic cohort study. - Little, P; Hobbs, F; Mant, D; McNulty, C; Mullee, M (2012)
BACKGROUND: Management of pharyngitis is commonly based on features which are thought to be associated with Lancefield group A beta-haemolytic streptococci (GABHS) but it is debatable which features best predict GABHS. Non-group A strains share major virulence factors with group A, but it is unclear how commonly they present and whether their presentation differs. AIM: To assess the incidence and clinical variables associated with streptococcal infections. DESIGN AND SETTING: Prospective diagnostic cohort study in UK primary care. METHOD: The presence of pathogenic streptococci from throat swabs was assessed among patients aged ≥5 years presenting with acute sore throat. RESULTS: Pathogenic streptococci were found in 204/597 patients (34%, 95% CI = 31 to 38%): 33% (68/204) were non-group A streptococci, mostly C (n = 29), G (n = 18) and B (n = 17); rarely D (n = 3) and Streptococcus pneumoniae (n = 1). Patients presented with similar features whether the streptococci were group A or non-group A. The features best predicting A, C or G beta-haemolytic streptococci were patient's assessment of severity (odds ratio [OR] for a bad sore throat 3.31, 95% CI = 1.24 to 8.83); doctors' assessment of severity (severely inflamed tonsils OR 2.28, 95% CI = 1.39 to 3.74); absence of a bad cough (OR 2.73, 95% CI = 1.56 to 4.76), absence of a coryza (OR 1.54, 95% CI = 0.99 to 2.41); and moderately bad or worse muscle aches (OR 2.20, 95% CI = 1.41 to 3.42). CONCLUSION: Non-group A strains commonly cause streptococcal sore throats, and present with similar symptomatic clinical features to group A streptococci. The best features to predict streptococcal sore throat presenting in primary care deserve revisiting.